2017
DOI: 10.1111/aas.13019
|View full text |Cite
|
Sign up to set email alerts
|

Spinal or general anaesthesia for lower‐limb amputation in peripheral artery disease – a retrospective cohort study

Abstract: Patients with spinal anaesthesia had a lower rate of surgical complications, re-operations and intensive care unit admissions. Patients with above-the-knee amputation and spinal anaesthesia had a lesser need for opioid medication in the post-operative period than patients with general anaesthesia. Anaesthesiologists performed neuraxial anaesthesia and/or analgesia in high-risk patients despite abnormal coagulation profile or ongoing anticoagulation, but no adverse outcomes were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Similarly, a retrospective cohort study demonstrated that spinal anaesthesia has lower complications and lower opiate requirements. 16 Another retrospective, single centre study over 10 years demonstrated lower post-operative pulmonary complications and cardiac dysrhythmias with RA compared with GA, but only spinal or epidural anaesthesia were used in that cohort. 17 Similar to other published data, 1 only 13% of patients in the present VQI cohort underwent RA.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a retrospective cohort study demonstrated that spinal anaesthesia has lower complications and lower opiate requirements. 16 Another retrospective, single centre study over 10 years demonstrated lower post-operative pulmonary complications and cardiac dysrhythmias with RA compared with GA, but only spinal or epidural anaesthesia were used in that cohort. 17 Similar to other published data, 1 only 13% of patients in the present VQI cohort underwent RA.…”
Section: Discussionmentioning
confidence: 98%
“…Induction of general anesthesia can also be challenging in older adults, given that aging is associated with several mental and physiological differences, as well as frequent coexistence of diseases. Therefore, many studies have suggested that spinal anesthesia can be used in lower limb surgery (e.g., hip, knee, and revascularization surgery) instead of general anesthesia [48][49][50][51][52]. Moreover, some studies have reported that spinal anesthesia results in lower rates of surgical complications, re-operations, and intensive care unit admissions, and may decrease 30-day mortality and the duration of hospitalization in patients undergoing lower limb surgery [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Another time trend reflected in our data is the development in the last decade of a significant rise in patients amputated using spinal anaesthesia to reduce postoperative complications and the need for opioid medication. 16 A strength of our study was the inclusion of all consecutive patients over an 8-year period. Another strength was the long follow-up time, allowing for calculation of both 2-year and 3-year survival rates.…”
Section: Discussionmentioning
confidence: 99%